Culture-specific notions of causation in Matses grammar - David W. Fleck (Journal de la Société des Américanistes)
Culture-specific notions of causation in Matses grammar. This paper looks at  the  linguistic coding of a typologically unusual type of causation in Matses, a Panoan language spoken in Amazonian Peru and Brazil. Specifically, the topic is the nominalizing suffix -anmës, whose function can be defined as specifying that: « the referent of the nominalization is an entity that non-volitionally, invisibly and often mysteriously causes helpless victims to enter some undesirable, enduring state ». This notion of causation appears to be particular to the Matses, suggesting that in addition to putative universal notions of causation, culture-specific notions of causal understanding should be taken into consideration in linguistic description.